Measurement of Absolute Monetary Poverty in Kazakhstan: a system of Indicators and Its Actualization Options - Pritvorova, T.P.; Gelashvili, N.N.; Temirbayeva, D.M.; Jazykbayeva, B.K. (BUKETOV BUSINESS REVIEW, 2023)
Relevance: To a great extent, poverty describes socio-economic situation of a part of the country’s population in a market economy and is the subject of research for global development organizations. Kazakhstan implements international statistical standards, however does not officially use a multitude of indicators that could be useful for the state policy of poverty reduction. Object: household whose income is below the poverty line. Purpose of the paper is to assess the range of poverty measurement indicators in Kazakhstan and the results obtained with their help from the standpoint of international statistical methodology to develop recommendations for their improvement in the context of state regulation needs. Methods: based on economic and statistical methods of analyzing the dynamics and structure of the Kazakh phenomenon recognized in world statistics as absolute monetary poverty. Findings: Over the past five years, the Sen-Shorrocks-Thon index has been showing a tendency of increase in all its constituent indicators: level, depth and sharpness. For the first time since 2013, its value for 2022 exceeds one. A twofold growth in the depth of poverty and an increase of its intensity by 2.5 times over this period indicates an increase in heterogeneity of the group with incomes below the subsistence minimum. In the regional context, poverty depth and intensity indicators show a unidirectional vector of changes. Regional analysis of assets ratio and Gini coefficients by decile groups of the population allows us to see values of these indicators in both northern and central regions of Kazakhstan, as well as the city of Almaty, higher than the average value of inequality across the country. The number of household members is a risk factor for falling into the social group of the poor while a significant proportion of fiveperson households are represented by families with children. Conclusions: There is a clear disproportion between groups with different numbers of children in terms of the share of the population with incomes below 40 thousand tenge. In the group of large families, the share of households with such income is three times greater than in the total population: 28.8% and 9.09%, respectively. To deepen the analysis of official statistics, indicators of chronic and child poverty are recommended, since they are of fundamental importance for assessing the results of social policy. We are planning an empirical sociological study to evaluate these indicators among the participants of a targeted social assistance program.